A genetically distinct lion (Panthera leo) population from Ethiopia - Bruche, S; Gusset, M; Lippold, S; Barnett, R; Eulenberger, K; Junhold, J; Driscoll, C; Hofreiter, M (Springer, 2012)
Lion (Panthera leo) numbers are in serious decline and two of only a handful of evolutionary significant units have already become extinct in the wild. However, there is continued debate about the genetic distinctiveness of different lion populations, a discussion delaying the initiation of conservation actions for endangered populations. Some lions from Ethiopia are phenotypically distinct from other extant lions in that the males possess an extensive dark mane. In this study, we investigated the microsatellite variation over ten loci in 15 lions from Addis Ababa Zoo in Ethiopia. A comparison with six wild lion populations identifies the Addis Ababa lions as being not only phenotypically but also genetically distinct from other lions. In addition, a comparison of the mitochondrial cytochrome b (CytB) gene sequence of these lions to sequences of wild lions of different origins supports the notion of their genetic uniqueness. Our examination of the genetic diversity of this captive lion population shows little effect of inbreeding. Immediate conservation actions, including a captive breeding programme designed to conserve genetic diversity and maintain the lineage, are urgently needed to preserve this unique lion population